2021
DOI: 10.1002/edm2.237
|View full text |Cite
|
Sign up to set email alerts
|

A novel data mining application to detect safety signals for newly approved medications in routine care of patients with diabetes

Abstract: Background: Clinical trials are often underpowered to detect serious but rare adverse events of a new medication. We applied a novel data mining tool to detect potential adverse events of canagliflozin, the first sodium glucose co-transporter 2 (SGLT2 inhibitor) in the United States, using real-world data from shortly after its market entry and before public awareness of its potential safety concerns.Methods: In a U. S. commercial claims dataset (29 March 2013-30 Sept 2015, two pairwise cohorts of patients ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 32 publications
(52 reference statements)
0
19
0
Order By: Relevance
“…RWD (Nordstrom et al, 2007;Gurulingappa et al, 2012a;Cao et al, 2013;Cheetham et al, 2014;Ferrajolo et al, 2014;Yeleswarapu et al, 2014;Whalen et al, 2018;Chapman et al, 2019;Choudhury et al, 2019;Wintzell et al, 2020;Fralick et al, 2021) and social media (Jimeno-Yepes et al, 2015;Powell et al, 2016;Cocos et al, 2017;Curtis et al, 2017;Pierce et al, 2017;Comfort et al, 2018;Gupta et al, 2018;Masino et al, 2018;Gavrielov-Yusim et al, 2019;Gartland et al, 2021) were the most frequent PV functions represented and, collectively, comprised 63% (21/33) of the papers included in the review. This is not surprising, as the use of social media to supplement PV activities began around 2009, with broader use of social media by the public, and attracted interest from both industry and academia as a potential source of safety-related events in near real time.…”
Section: Major Trends and Opportunities In Industry Application Of Ml...mentioning
confidence: 99%
“…RWD (Nordstrom et al, 2007;Gurulingappa et al, 2012a;Cao et al, 2013;Cheetham et al, 2014;Ferrajolo et al, 2014;Yeleswarapu et al, 2014;Whalen et al, 2018;Chapman et al, 2019;Choudhury et al, 2019;Wintzell et al, 2020;Fralick et al, 2021) and social media (Jimeno-Yepes et al, 2015;Powell et al, 2016;Cocos et al, 2017;Curtis et al, 2017;Pierce et al, 2017;Comfort et al, 2018;Gupta et al, 2018;Masino et al, 2018;Gavrielov-Yusim et al, 2019;Gartland et al, 2021) were the most frequent PV functions represented and, collectively, comprised 63% (21/33) of the papers included in the review. This is not surprising, as the use of social media to supplement PV activities began around 2009, with broader use of social media by the public, and attracted interest from both industry and academia as a potential source of safety-related events in near real time.…”
Section: Major Trends and Opportunities In Industry Application Of Ml...mentioning
confidence: 99%
“…The results of this study showed that TreeScan identified 29 positive signals from the raw data, of which 9 were true positives when compared with the standard signals. Previous studies on TreeScan have primarily been qualitative evaluations of its results 7,17–19 . For example, Kulldorff et al .…”
Section: Discussionmentioning
confidence: 99%
“…DISCUSSIONThe results of this study showed that TreeScan identified 29 positive signals from the raw data, of which 9 were true positives when compared with the standard signals. Previous studies on TreeScan have primarily been qualitative evaluations of its results 7,[17][18][19]. For example, Kulldorff et al used the TreeScan method to uncover adverse reaction signals for 2 antifungal agents (terbinafine and itraconazole) and 2 thiazolidinediones (pioglitazone and rosiglitazone), resulting in 5 of the 10 identified signals being classified as adverse reactions, including liver damage, allergic reactions, nausea and vomiting.…”
mentioning
confidence: 99%
“…As part of a signal identification process, TreeScan can be used to detect a wide range of potential adverse events that can be further assessed to determine clinical plausibility and followed up with targeted safety studies. TreeScan has been used successfully in applications of vaccine safety 3–8 and monitoring of medication safety in pediatric 9 and adult populations 10 …”
Section: Introductionmentioning
confidence: 99%
“…TreeScan has been used successfully in applications of vaccine safety [3][4][5][6][7][8] and monitoring of medication safety in pediatric 9 and adult populations. 10 Given the limitations of the current methods of monitoring the safety of medications used during pregnancy, TreeScan could be particularly useful in the field of perinatal pharmacoepidemiology. 11 Pregnant women are rarely included in clinical trials during drug development, resulting in gaps in knowledge of safety and effectiveness that have to be addressed in postmarketing surveillance.…”
Section: Introductionmentioning
confidence: 99%